2023
DOI: 10.1111/aphw.12473
|View full text |Cite
|
Sign up to set email alerts
|

What works in peer support for breast cancer survivors: A qualitative systematic review and meta‐ethnography

Abstract: Breast cancer is associated with adverse physical and psychological consequences. Although research has identified the various benefits linked to psychosocial interventions, mixed results have been found in relation to peer support. The aim of the present systematic review and meta‐ethnography is to explore the qualitative evidence on the experience of breast cancer survivors in peer support. A systematic search of the literature was conducted until June 2023, and a meta‐ethnographic approach was used to synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…However, as mentioned earlier, Comunitats offers psychoeducational resources and involves the participation of healthcare professionals who can correct information if needed or guide participants to the appropriate information source if the question exceeds the scope of the support community. Survivors reported ' nding recognition' in online community interactions, aligning with prior research emphasizing that PS fosters mutual understanding and recognition through shared experiences [13,16]. Based on our research ndings, 'helping others' is the process that occurred to the least extent.…”
Section: Relationships Between Empowerment and Other Related Variablessupporting
confidence: 85%
See 1 more Smart Citation
“…However, as mentioned earlier, Comunitats offers psychoeducational resources and involves the participation of healthcare professionals who can correct information if needed or guide participants to the appropriate information source if the question exceeds the scope of the support community. Survivors reported ' nding recognition' in online community interactions, aligning with prior research emphasizing that PS fosters mutual understanding and recognition through shared experiences [13,16]. Based on our research ndings, 'helping others' is the process that occurred to the least extent.…”
Section: Relationships Between Empowerment and Other Related Variablessupporting
confidence: 85%
“…Although research on the impact of PS on oncology patients does not lead to conclusive results, BC patients are often interested in knowing the experience of other patients who undergo similar situations [11,12]. Some studies suggest that PS can create a safe space leading to emotional support and mutual understanding [13]. Furthermore, interaction among patients beyond the support group, can alleviate feelings of loneliness and isolation [14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the de nition of the National Cancer Institute (NCI), social support is a network of family, friends, neighbors, and community members that is available in times of need to give psychological, physical, and nancial help [ 16] .Studies had shown that social support helps patients to counteract the effects of depression, anxiety, and other negative psychological in uences by strengthening their own management behaviors [ 17][18] .Family support signi cantly and negatively correlated with patients' anxiety and depression [ 19] ;Peer support can relieve patients' negative emotions while guarantee the realization of self-worth and improve self-identity [ 20] [21] .Therefore, it's essential to build a communication platform, establish a WeChat group and actively carry out a patient communication meeting, which can help patients to improve communication and obtain a sense of group comfort. Besides, nurses should timely feedback patients' condition to their families to enhance family support.…”
Section: Discussionmentioning
confidence: 99%